The Influence of Competence and Work Experience on Position Promotion through Job Performance at PT. Bank Sumut Head Office - M Randy Gunawan; R sabrina; Satria Tirtayasa; Muis Fauzi Rambe (Jurnal Mantik, 2022)
The purpose of this study was to determine and analyze the effect of competence and promotion on job promotion through promotion at PT. Bank Sumut Medan head office. The sample in this study uses the 10% slovin formula for as many as 87 employees, where the population of all employees is 675 employees. The data collection technique in this study used the questionnaire method, while the data analysis technique in this study used a quantitative approach, with SEM-PLS statistical analysis. Data processing in this study using the software program SmartPLS 3.3.3. The results of this study prove that competence directly has a positive but not significant effect on employee promotions, directly work experience has a positive and significant effect on employee promotions, directly work performance has a positive and significant effect on promotions, and direct competence has a positive and significant effect on work performance, directly work experience has a positive and significant effect on work performance, indirectly competence has a positive and significant effect on promotion through work performance, indirectly work experience has a positive and significant effect on promotion through position promotion. This shows that work performance it can affect competence towards promotions and through work performance, it can affect work experience towards promotions in positions PT. Bank Sumut Medan Head Office.